2012
DOI: 10.1007/s00011-012-0497-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen suppresses heptatic IκB expression during short-term alcohol exposure

Abstract: Estrogen exposure enhances alcohol-induced liver inflammation, and the anti-inflammatory effects of testosterone in the liver might be related to induction of IκB. Elevated inflammation in response to estrogen may overwhelm the regenerative influence of IL-6 in liver, leading to increased steatosis and greater liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…There are some interesting findings on sex differences of NFkB activity, with most focusing on hepatic activity. In one study, ovariectomized female rats receiving constant estrogen administration had decreased hepatic IKB mRNA expression and increased NFkB activity following alcohol consumption compared with controls and rats receiving testosterone (Lee et al, 2012). In another study, chronic ethanol administration was found to increase hepatic levels of NFkB in female rats to a greater extent than males, a finding that may explain why alcohol-induced liver injuries are more prevalent in the females (Kono et al, 2000).…”
Section: Nfkb and Inflammation In Alcohol Abusementioning
confidence: 99%
“…There are some interesting findings on sex differences of NFkB activity, with most focusing on hepatic activity. In one study, ovariectomized female rats receiving constant estrogen administration had decreased hepatic IKB mRNA expression and increased NFkB activity following alcohol consumption compared with controls and rats receiving testosterone (Lee et al, 2012). In another study, chronic ethanol administration was found to increase hepatic levels of NFkB in female rats to a greater extent than males, a finding that may explain why alcohol-induced liver injuries are more prevalent in the females (Kono et al, 2000).…”
Section: Nfkb and Inflammation In Alcohol Abusementioning
confidence: 99%
“…Grossman's research firstly showed the low testosterone levels were associated with poor prognosis in chronic liver diseases in 2012 ( 10 ) and 2016 ( 9 ) and Klair revealed that estrogen deficiency could increase fibrosis risk among postmenopausal women with NAFLD in 2016 ( 30 ). As for the underlying mechanism, Lee et al and Kim et al clarified that estrogen and estrogen-related receptor γ(ERRγ) affected the progression of ALD respectively via hepatic IκB ( 31 ) and CB1R-CYP2E1-mediated oxidative stress ( 15 ). Li et al proved that Foxa1/a2 played essential roles in sexual dimorphism of HCC in 2012 ( 32 ) and Zhang et al suggested that overexpression of nuclear androgen receptor driven by PI3K-AKT- mTOR pathway was associated with progression and prognosis of HCC in 2018 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a previous study performed using MCF-7 cells suggested that this increase was related to the increase of p105 protein level ( 57 ) . On the other hand, another research group showed that estrogen treatment decreased liver IkB mRNA and protein expression and also increased ethanol-induced liver NF-kB levels and TNF-α expression ( 58 ) . These disparate findings are likely to be related to the cell-specific effects of estrogen and merit further analysis.…”
Section: Discussionmentioning
confidence: 99%